Extend Nearly Pseudo Quasi-2-Absorbing submodules(I) - Abdullah, Omer; Karim Mohammadali, Haibat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The concept of a 2-Absorbing submodule is considered as an essential feature in the field of module theory and has many generalizations. This articale discusses the concept of the Extend Nearly Pseudo Quasi-2-Absorbing submodules and their relationship to the 2-Absorbing submodule, Quasi-2-Absorbing submodule, Nearly-2-Absorbing submodule, Pseudo-2-Absorbing submodule, and the rest of the other concepts previously studied. The relationship between them has been studied, explaining that the opposite is not true and that under certain conditions the opposite becomes true. This article aims to study this concept and gives the most important propositions, characterizations, remarks, examples, lemmas, and observations related to it. In the end, we will present a very important equivalent of our concept with the rest of the concepts presented previously.